2014
DOI: 10.3109/21691401.2014.955106
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic nanoparticles: Recompense, cellular uptake and toxicity concerns

Abstract: Over the past few years, nanoparticles and their role in drug delivery have been the centre of attraction as new drug delivery systems. Various forms of nanosystems have been designed, such as nanoclays, scaffolds and nanotubes, having numerous applications in areas such as drug loading, target cell uptake, bioassay and imaging. The present study discusses various types of nanoparticles, with special emphasis on ceramic nanocarriers. Ceramic materials have high mechanical strength, good body response and low o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 62 publications
0
44
0
Order By: Relevance
“…In vivo experiments have revealed that carbon nanotubes are found to cause dose-dependent epithelioid granulomatous lesions in the lung and persistent interstitial inflammation on chronic exposure [ 40 , 41 ]. Furthermore, ceramic nanoparticles, commonly used for drug delivery, have been reported to exhibit oxidative stress/cytotoxic activity in the lungs, liver, heart, and brain, as well as have teratogenic/carcinogenic effects [ 42 ].…”
Section: Toxicity Of Nanoparticlesmentioning
confidence: 99%
“…In vivo experiments have revealed that carbon nanotubes are found to cause dose-dependent epithelioid granulomatous lesions in the lung and persistent interstitial inflammation on chronic exposure [ 40 , 41 ]. Furthermore, ceramic nanoparticles, commonly used for drug delivery, have been reported to exhibit oxidative stress/cytotoxic activity in the lungs, liver, heart, and brain, as well as have teratogenic/carcinogenic effects [ 42 ].…”
Section: Toxicity Of Nanoparticlesmentioning
confidence: 99%
“…In the context of the ceramic industry, many reports show that occupational exposure to ceramic dusts and fibres is associated with chronic bronchitis, chronic obstructive pulmonary disease, reduced lung function, wheezing, breathlessness and dry cough (Jaakkola et al, 2011;Kargar et al, 2013;Trethowan et al, 1995). (Bakand et al, 2012;Li et al, 2010;Paur et al, 2011;Pietroiusti et al, 2018 ;Stone et al, 2017 (Singh et al, 2016).…”
Section: General Remarksmentioning
confidence: 99%
“…The components most commonly used in ceramic nanoparticles are silica and aluminum. However, the core of these nanoparticles is not limited to these two materials; in fact, they can be composed of a combination of metallic and nonmetallic materials [ 28 ]. For instance, CeO 2 -capped mesoporous silica nanoparticles (MSN) have been developed to act as vehicles for drug delivery by releasing β -cyclodextrin into lung cancer cells [ 29 ].…”
Section: Nanoparticles In Medicinementioning
confidence: 99%